The Concept Learning Science Skills in Kindergarten Age Children - Ashar, Ashar; Idamayanti, Reski (ARRUS Journal of Social Sciences and Humanities, 2023)
literature or other sources that are relevant to the research objectives. The results of the concept of learning science skills in kindergarten-aged children involve an active, explorative, and discovery-based approach. Several important concepts that can be applied to learning science skills, including inquiry (invention) approaches, problem-based learning, collaborative learning, observation and experimentation, critical thinking skills, communication and representation concepts, learning concepts related to everyday life. Learning science skills in kindergarten provides a solid foundation for children to understand science concepts, such as developing observing skills, comparing skills, classifying skills, measuring skills, communicating skills, asking questions, experimenting skills